Combined effect of steel fiber and metakaolin incorporation on mechanical properties of concrete - Mermerdas, Kasim; Guneyisi, Erhan; Gesoglu, Mehmet; Akoi, Arass Omer Mawlod (ELSEVIER SCI LTD, 2014)
This study reports the results of an experimental study on mechanical properties of plain and metakaolin (MK) concretes with and without steel fiber. To develop the metakaolin included steel fiber reinforced concrete mixtures, Portland cement was partially replaced with MK as 10% by weight of the total binder content. Two types of hook ended steel fibers with length/aspect ratios of 60/80 and 30/40 were utilized to produce fiber reinforced concretes. Two series of concrete groups were designed with water to binder ratios (w/b) of 0.35 and 0.50. The effectiveness of MK and different types of steel reinforcement on the compressive, flexural, splitting, and bonding strength of the concretes were investigated. All tests were conducted at the end of 28 days of curing period. Analyses of variance on the experimental results were carried out and the levels of the significance of the variables on the mechanical characteristics of the concretes were determined. Moreover, correlation between the measured parameters was carried out to better understand the interaction between mechanical properties of the concretes. The results revealed that incorporation of MK and utilization of different types of steel fibers significantly affected the mechanical properties of the concretes, irrespective of w/b ratio. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Ceramic matrix composites; Mechanical properties; Strength; Steel fiber reinforced concrete